PENGARUH KONFLIK KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. CAHAYA MINI GROSIR DENPASAR - Ni Luh Nikmawati Dewi; Nengah Landra; Ni Made Dwi Puspitawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
The existence of work conflict can affect employee performance because it begins to decline in employee performance levels and the occurrence of misunderstandings between employees such as lack of communication. The work environment must also be considered due to lack of lighting, inadequate space for movement, lack of harmonious relations between employees and other employees, causing discomfort at work. This study aims to determine and analyze the effect of work conflict and work environment on employee performance at CV. Cahaya Mini Grosir Denpasar. The population in this study were all employees of CV. Cahaya Mini Grosir Denpasar as well as the sampling of this research as many as 30 people. The analytical method used is Multiple Linear Regression Analysis. The results showed that work conflict had a negative effect on employee performance and the work environment had a positive effect on employee performance. Future researchers are expected to be able to add other factors that affect employee performance such as motivation, leadership and work discipline.